Model of Disaster Information Cycle of West Java Television Journalists - Septiawan Santana Kurnia; Dadi Ahmadi; Satya Indra Karsa; Doddy Iskandar; Firmansyah Firmansyah (Ikatan Sarjana Komunikasi Indonesia, 2020)
Disaster information is an important factor in disaster management efforts, including in West Java. It helps officers and the community to immediately anticipate disasters that may occur. Journalists are among those who play a role in disseminating disaster information. This study aims to describe disaster information cycle model of West Java television journalists in obtaining and disseminating disaster information with the help of technology to increase the speed. This research applies a qualitative method, namely a case study to describe a usage model of disaster information seeking which is uniquely influenced by the developments in information technology. Data collection is carried out through observation, interviews, and documentation. This study finds that smartphone technology contributes to the dissemination of disaster information by television journalists through providing access to social media, online media, and information in group chats. There is an interrelated flow of information between journalists, television editors, local governments, officials and the community. Participation of public and journalists in obtaining and disseminating disaster information helps the government and officers to find out the real conditions of disaster locations and how to handle them.